TINJAUAN ULANG PERHITUNGAN PENULANGAN STRUKTUR BETON BERTULANG PADA GEDUNG BANK NTB SYARIAH MENGGUNAKAN METODE SNI 2847:2019 - Husainy, Zainuddin; Nafi, Aunun (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
Ruang Publik Kreatif (RPK) is an open area located at the Sumbawa University of Technology (UTS) which is used for many outdoor activities. The RPK Hall was built with steel portal construction so it was deemed necessary to check the strength of the structure to ensure that it had a safe truss structure. Calculations for the truss structure will use the Frame3DD application which is much lighter than other structural calculation applications. This research resulted in a recommendation to replace CNP 100 profile curtains with CNP 150 profile curtains because the installed profile did not comply with the deflection limit and allowable moment limit. 2. Installed truss profile changed from WF250x125x6x9 to WF298x149x5.5x8 on elements 1 and 8, WF200x100x5.5x8 to WF298x149x5.5x8 on elements 2 and 7, WF100x50x5x7 to WF150x75x5x7 on elements 3 and 6, WF10 0x50x5x7 becomes WF125x60x6x8 on elements 4 and 5, and WF250x125x6x9 became WF200x100x5.5x8, and all of them resulted in at least a 29% increase in raw material costs from the initial RPK construction budget.